The Sweet and Sour of the Sugar-Sweetened Beverage Tax - Khamis, Al-Alawy; Azaad Immanuel, Moonesar,; Shatha, Muhsineh; Reem, Gaafar; Bashir, and Aden (International Journal of Nutrition, 2021)
Obesity is a common and preventable Non-Communicable Disease that is of great importance. Population-based interventions are recognised to have a profound effect on improving health outcomes. One of these approaches includes the adoption of the Sugar-Sweetened Beverage (SSB) Tax. Objectives There were three objectives, 1) explore the associations between gender, age, nationality, and change in SSB consumption, 2) explore SSB consumption during Covid-19 lockdown, and 3) inform policy decision making. Methods A cross-sectional survey in the United Arab Emirates. We performed descriptive analysis and chi-square for independence to test the difference between the expected and the observed frequencies in one or more categories. Results Since the introduction of SSB tax, change in SSB consumption by gender, age or nationality was not statistically significant. Further analysis of the proportion of sugar intake per day was statistically significant (P-value <0.001) by nationality. There was no statistically significant change in SSB consumption by age, gender, or nationality during the Covid-19 lockdown. Further analysis within the group that reported change in SSB consumption suggests a majority (80.5%) reported a reduction in SSB consumption. Conclusions Change in SSB consumption by gender, age or nationality was not statistically significant since the introduction of SSB tax, or during Covid-19 lock-down; thus, we accept the Null Hypothesis. Imposing a levy on frequently consumed SSB or revisiting levy by the gram, volume, or type of added sugar (or in combination) may prove to be more effective in reducing SSB consumption. Further research is needed to determine the extent other demographic factors influence SSB consumption as well as the enablers and barriers associated with SSB consumption.
Keywords: Sugar-Sweetened Beverages; Demographics; Health Policy; Public Health; United Arab Emirates